Rancang Bangun Alat Pendeteksi Suhu Tubuh Menggunakan Nodemcu Berbasis Web - Muhammad Ghaffaar Ramadhan; Dadan Ramdan; Habib Satria (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2022)
The COVID-19 pandemic has made indonesian people have to follow all health protocols made by the government, to overcome this virus requires movement of all sectors, including the research sector. The research sector is not only engaged in vaccines and drugs but also in efforts to reduce the spread of COVID 19 in Indonesia. This study aims to produce an RFID body temperature and attendance detection tool system using a web-based NodeMcu and produce a program that will send data to the web server. This tool is designed to be able to check body temperature and attendance more accurately and can be monitored directly by the user. The results of the study can directly detect body temperature using the MLX90614 body temperature sensor when someone approaches the sensor, the proxymity sensor will directly order the pump to remove the hand sanitizer liquid, and the RFID Reader detects the presence or attendance using the RFID Card. All data will appear on the LCD and enter the cloud server and will appear on the web page so that it can make it easier for users to carry out attendance activities in daily activities.